Singing As An Effective Approach For Learning English On Early Childhood - Ro'ifah Ro'ifah (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2019)
There are so many native languages in Indonesia that makes English as a foreign language following Indonesian as the L2. This leads to the development of simultaneous bilinguals. However, there have been some contradictory opinions on whether learning English for early childhood is effective as it can inhibit a child’s L1 and L2 development. This may lead to the phenomenon of subtractive bilingualism resulting in a major dilemma for the government and parents. However, this notion can be debated through the critical period hypothesis. This study presents a literature review on ‘rhymes, songs, and chant’s as the effective media for learning English and its implication for early childhood through ‘singing’ approach.